2004
DOI: 10.1111/j.1464-5491.2004.01282.x
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes mellitus in childhood: a matched case control study in Lancashire and Cumbria, UK

Abstract: Many of the results are consistent with the hygiene hypothesis which links improved living standards with decreased exposure to microorganisms and increased risk of immune mediated disease in childhood. These findings challenge the idea that improved hygiene acts exclusively through a Th2 mechanism leading to atopic disease as Type 1 DM is mediated by a Th1 reaction. The association with maternal smoking could be due to recall bias but a causal link cannot be excluded with confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 38 publications
6
65
5
Order By: Relevance
“…We could not confirm all results of a recent case-control study from the U.K. (34) where older siblings and regular contact to pets were associated with a reduced risk of type 1 diabetes. In our study, only regular contact to dogs was inversely but not significantly related to case status (P ϭ 0.07).…”
Section: Discussioncontrasting
confidence: 55%
“…We could not confirm all results of a recent case-control study from the U.K. (34) where older siblings and regular contact to pets were associated with a reduced risk of type 1 diabetes. In our study, only regular contact to dogs was inversely but not significantly related to case status (P ϭ 0.07).…”
Section: Discussioncontrasting
confidence: 55%
“…The findings of this research seem inconsistent, as some studies have concluded that high birthweight is associated with increased diabetes risk [8] or reduced diabetes risk [9], while others have shown no association with type 1 diabetes risk [10]. Interpretation of these findings is made more difficult because studies have reported associations using many different categorisations of birthweight [8,[11][12][13][14], with some [15,16] only reporting findings for the extremes of birthweight and others [17][18][19][20][21] not reporting their birthweight results in any detail, concentrating instead on other findings. This could lead to reporting bias if the decision to report birthweight findings was influenced by whether or not results were interesting or 'statistically significant'.…”
Section: Introductionmentioning
confidence: 72%
“…The precise mechanism(s) by which smoking affects serum immunoglobulin levels and the component(s) of cigarette smoke responsible for the effect have not been clarified (17). However, evidence of a smoke-response relationship, with lower levels of IgG with increased smoking, has been presented (18)(19)(20)(21). In this study, we found another smokeresponse relationship with lower levels of IgM in diabetic pregnant women.…”
Section: Discussionmentioning
confidence: 49%